Drinking Watermelon Juice Shift the Gut Microbiome in Diabetic Mice (P20-025-19). (13th June 2019) - Wong, Siau Yen; Wu, Lei; Lu, Peiran; Ojo, Babajide; Tang, Minghua; Clarke, Stephen; Keirns, Bryant; Lucas, Edralin A; Smith, Brenda; Chowanadisai, Winyoo; Conway, Tyrrell; Lin, Dingbo
Abstract: Objectives: Watermelon is a delicious and healthy fruit that contains low calories and is rich in carotenoids, vitamin A, vitamin C, citrulline, and other bioactive compounds. The health benefits of watermelon in diabetes are poorly understood. In the current study, we sought to determine the effects of watermelon juice on gut microbiome profile and blood glucose management in type 1 and type 2 diabetic mice. Methods: Six-week-old male C57BL/6 J wild type (WT), db/db type 2 diabetic (db/db), and streptozocin (STZ)-induced type 1 (STZ) diabetic mice were fed a chow diet and given 50% or 100% watermelon juice or tape water during night cycle for 8 weeks. At the termination of the study, mice were fasted for 3 hrs prior to euthanization. Blood, cecal contents, and other tissues were collected for laboratory assessments. Plasma metabolic parameters and pro-inflammatory cytokines were monitored by a clinical analyzer and ELISA, respectively. Cecal microbiome was profiled by 16S rRNA sequencing and followed by bioinformatic analysis. Results: Consumption of watermelon juice significantly lowered fasting blood glucose levels in both diabetic mouse models. The fasting insulin level was significantly decreased in db/db consuming watermelon juice, though it was undetectable in STZ mice, with or without watermelon juice. Drinking watermelon juice tremendously changed the gut microbiome composition. At the phylum level, the Firmicutes/Bacteroidetes ratio was significantly associated with genotype (e.g., WT vs STZ vs db/db) and diet (e.g., watermelon juice vs tap water). At the genus level, abundances of Ruminiclostridium_9, Parasutterella, and Clostridium_sensu_stricto_1 were increased in STZ mice with watermelon, and abundances of Oscillibacter and Ruminiclostridium were decreased in db/db mice with watermelon. Watermelon juice induced gut microbiome compositional changes also occurred at the species level. Conclusions: Watermelon juice intervention causes a decrease in blood glucose level and shifts of the gut microbiome in both type 1 and type 2 mice. Funding Sources: National watermelon board grant.